Caracterização da resistência a antimicrobianos em isolados de Salmonella enterica provenientes de materiais de origem avícola - Mattiello, Samara Paula (2013)
Salmonella enterica is an important pathogen that causes gastroenteritis, and is transmitted to human through the consumption of contaminated food, especially from animal origin. The use of antimicrobials for therapeutic purposes in veterinary medicine and as growth promoters in animals used for food production has been considered one of the causes of emergence and spread of multi-drug resistant (MDR) S. enterica, representing a major risk to public health. Thus, the aim of this study was to determine antimicrobial resistance profiles as well as to characterize the main determinants involved on phenotypes of resistance in S. enterica isolates from poultry by-product meal and from other samples derived of poultry production chain, especially from environment of broiler houses. A total of 203 S. enterica isolates was analyzed, being 106 from poultry by-product meal and 97 isolated mainly from drag swabs. Higher percentages of resistance were detected in S. enterica isolated from drag swab when compared with isolates from poultry by-product meal. The highest percentages of resistance were found to sulfonamides followed by tetracycline, trimethoprim-sulfamethoxazole, nalidixic acid, streptomycin and spectinomycin. The majority of isolates was sensitive to ciprofloxacin and enrofloxacin. MDR phenotypes were detected in 37 (18.2%) isolates and the profile penta-resistant (ampicillin, chloramphenicol, streptomycin, tetracycline and sulphamethoxazole) was detected in S. Heidelberg, S. Cerro and two S. Senftenberg. Class 1 integrons was found in 26 isolates (12.7 %), and did not detect the presence of class 2 integron. A S. Senftenberg isolated from environment was found to harbor two class 1 integrons: one integron with a typical 3 CS, and the other with an atypical 3′CS linked to the qacH sul3. The sul1, sul2 and sul3 genes were detected in 18.7%, 32.5% and 31.2% S. enterica phenotypically resistant to sulfonamide, respectively. blaCMY, blaCTX-M and blaTEM genes were detected in 23.8%, 9.5% and 85.7% of isolates resistant to β -lactams, respectively. Resistance determinants tetA, tetB and tetC were observed in 70%, 10% and 10% of isolates resistant to tetracycline, respectively. aadA and aadB genes were detected in 26.1% and 32.1% of isolates resistant to aminoglycosides, as well as the presence of strA and strB genes in 44.4% and 34.9% of S. enterica isolates phenotypically resistant to streptomycin. The presence of a heterogeneous profile of antimicrobial determinants and mobile genetic elements in the isolates analyzed indicates the potential risk that these bacteria represent to human health.